Diabetes and autistic spectrum disorder – diagnostic and management challenges. (24th May 2012) - Webster, C; Greene, S; Alexander, V
Abstract : Clinical presentation: A 13 year old boy with known severe autistic spectrum disorder presented with a short history of polyuria and polydipsia. He has a family history of sensorineural deafness affecting his mother and maternal grandfather, but he appears to have normal hearing. He attends a residential school and spends the holidays at home with his mother and brother in a remote area. On examination he was not obese, did not have acanthosis nigracans, and had no dysmorphic features, detailed examination was limited due to difficulties with communication and behaviour. Investigations: Fasting blood glucose was 14.5 mmol/l, with no ketonuria. Further investigations were carried out under sedation. The results of these were HbA1c 92 mmol/mol, insulin 8 mU/l, C peptide 0.69 nmol/l, lactate 4.1 mmol/l. Genetics were negative for maternally inherited diabetes and deafness. Management: Initial treatment was commenced with gliclazide due to potential difficulties in insulin administration and uncertainty re diagnosis. Due to significant weight loss and ongoing symptoms insulin was subsequently started and is currently administered by school staff. Progress: Over time he has had increasing insulin requirements and is currently on 0.25 units/kg/day, but remains ketone free. To date there have been no problems with hypoglycaemia. Risperidone has recently been commenced in order to try and calm aggression and agitation. Anti-GAD antibodies and anti-IA2 antibodies have recently been confirmed at 84.4 U/ml and 96.6 U/ml respectively, supporting a diagnosis of type 1 diabetes. The main clinical challenge is now to manage diabetes during the periods the young person spends at home. Whilst he has had a prolonged (6 weeks) holiday spent at home where he received no insulin, this is not going to be sustainable in the long term as he will be at risk of diabetic ketoacidosis. There is a clear need for consistency in the personnel working with him and in their approach to his management. The challenge, to bridge the gap between school and homecare, is being addressed by a multi-disciplinary team including Child and Adolescent Mental Health Services, social work, school health and advocacy services.